ECONOMIC AND MATHEMATICAL METHODS OF CONDUCTING INTERNAL AUDITS IN A SANATORIUM-WELLNESS INSTITUTION (Neo Scientific Peer Reviewed Journal, 2024)
This article covers the assessment of the activities of the service of internal audit of a sanatorium-wellness institution, the development of a methodology, as well as scientific-practical and economic-mathematical methods.The economic feasibility of activities in a sanatorium-wellness institution was assessed, the factors affecting the results of ordinary and other activities were determined by internal auditors, the method of internal audit was studied economic activity, reflected in Accounting, Financial Reporting and tax accounting. As a result of the analysis of the financial and economic activities of economic entities, the organization of the Internal audit Service, a system was created that analyzes the possibilities of increasing the effectiveness of its activities. This makes it possible to qualitatively evaluate the effective activities of the internal audit of the sanatorium-wellness institution and the provision of internal control.